Efektivitas Penggunaan Media GeoGebra pada Pembelajaran Matematika Materi Grafik Fungsi Kuadrat - Usman, Muhammad Rizal; Satriani, Sri; Ibrahim, Muhaiminah (JURNAL MathEdu (Mathematic Education Journal), 2023)
The research aims to determine the effectiveness of using GeoGebra media on mathematical learning of quadratic functions graph material. This type of research is a pre-experimental study with a one group pretest-posttest design. The sample in this study was class X students at SMK Muhammadiyah 4 Tallo, totaling 17 students. The research instruments used were learning achievement tests, student activity observation sheets and learning implementation, and student response questionnaires. Data analysis in this study is descriptive analysis and inferential analysis. The results of this study indicate that GeoGebra media is effectively used on mathematical learning of quadratic functions graph material with an average score of 85.17 for student learning outcomes. Student learning outcomes complete classically with a percentage of 82.35%. The student's normalized gain is in the high category with a value of 0.81. The average percentage of student activity was 84.43% and the response with a percentage of 96.83% of students gave a positive response.